2019
DOI: 10.1007/s40263-019-00690-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Pediatric Convulsive Status Epilepticus

Abstract: Convulsive status epilepticus (CSE) is one of the most common pediatric neurological emergencies. Ongoing seizure activity is a dynamic process and may be associated with progressive impairment of gamma-aminobutyric acid (GABA)-mediated inhibition due to rapid internalization of GABA A receptors. Further hyperexcitability may be caused by AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) and NMDA (N-methyl-d-aspartic acid) receptors moving from subsynaptic sites to the synaptic membrane. Receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 136 publications
1
41
0
4
Order By: Relevance
“…A recent review of 17 studies evidenced a remarkable nonadherence to recommended dosages, timing, and number of administrations in up to 61% of patients treated with benzodiazepines, even if they represent first-line treatments without further valid therapeutic alternatives. 19 Three recent trials (ConSEPT, EcLiPSE, and ESETT) demonstrated that levetiracetam and valproate have the same effectiveness and safety of phenytoin as second-line treatments. [20][21][22] Levetiracetam is preferred over phenytoin by a growing number of physicians because of advantages in terms of administration rapidity (5 vs. 20 minutes) and less serious side effects.…”
Section: Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of 17 studies evidenced a remarkable nonadherence to recommended dosages, timing, and number of administrations in up to 61% of patients treated with benzodiazepines, even if they represent first-line treatments without further valid therapeutic alternatives. 19 Three recent trials (ConSEPT, EcLiPSE, and ESETT) demonstrated that levetiracetam and valproate have the same effectiveness and safety of phenytoin as second-line treatments. [20][21][22] Levetiracetam is preferred over phenytoin by a growing number of physicians because of advantages in terms of administration rapidity (5 vs. 20 minutes) and less serious side effects.…”
Section: Status Epilepticusmentioning
confidence: 99%
“…23 Ketamine avoided endotracheal intubation in a significant proportion of children with refractory status epilepticus in recently reported case series and case reports. 19,24 These positive results might result from the antagonist effect of ketamine on the overexpression of N-methyl-D-aspartate receptors during the late stages of status epilepticus. 23…”
Section: Status Epilepticusmentioning
confidence: 99%
“…10 mg) may repeat dose once aŌer ~10 min 5 mg (<15 kg), 10 mg (>15 kg) off-label alternaƟves: nasal or intramuscular midazolam, nasal or buccal lorazepam Early-phase treatment in hospital choose one of the following benzodiazepines if max dose not given yet*: Diazepam is lipophilic and, thus, rapidly penetrates the blood-brain barrier leading to rapid onset of action with a first effect after few minutes and a maximum effect expected after 10-20 min (half-life 20-100 h) (Singh et al 2020). Buccal midazolam is given at 0.2-0.5 mg/kg (maximum single dose 10 mg, maximum two doses; proposed doses: 3 months -< 1 year 2.5 mg, 1 -<5 years 5 mg, 5-<10 years 7.5 mg, >10 years 10 mg) with a maximum effect expected after approximately 10 min and a shorter half-life than diazepam of 3-4 h (Singh et al 2020). Which of these drugs is more superior remains a matter of debate.…”
Section: -10 Minmentioning
confidence: 99%
“…Which of these drugs is more superior remains a matter of debate. In a recent Cochrane review on drug management of children with tonic-clonic seizures including convulsive SE, no sufficient evidence was found when comparing rectal diazepam to buccal midazolam for treatment of acute tonic-clonic seizures (Singh et al 2020). Buccal midazolam has been reported to be at least as effective in cessation of SE, equally safe, and also more socially acceptable than rectal diazepam (Scott et al 2012;Mpimbaza et al 2008;Brigo et al 2015;McTague et al 2018b;Capovilla et al 2013;McMullan et al 2010;McIntyre et al 2005).…”
Section: -10 Minmentioning
confidence: 99%
“…The relationship that was demonstrated between aetiologies of status epilepticus and prognosis represents an important stimulus for the realization of an adequate diagnostic work-up, but the prevention of mortal outcome or permanent neurological dysfunctions requires optimization of the available antiseizure medications [1,2,3,4,5]. The therapeutic approach that is described in the paper reflects national or single-centre protocols as well as the state of knowledge in the analysed temporal range (2013-2015) [1].…”
mentioning
confidence: 99%